AN ACCREDITED PHOTONIC ENGINEERING PROGRAMME: A NOTABLE EXPERIENCE - Shazlina Johari; Wan Mokhdzani Wan Nor Haimi; Ong Siok Lan; Nur Juliana Juhari; Rizalafande Che Ismail; Shahrir Rizal Kasjoo; Mohamad Nazri Abdul Halif; Muammar Mohamad Isa; Nurul Izza Mohd Nor; Norhayati Sabani, (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2025)
In most institutions of higher learning in Malaysia, photonic engineering is a field that is often offered at the postgraduate level. However, UniMAP took the initiative by offering the Photonic Engineering program at the undergraduate level and UniMAP was the only public university to offer Photonic Engineering Programme for undergraduates in Malaysia. This is in line with the current direction of the Malaysian government and electronic industry to further enhance research in the photonic field. The primary objective of this paper is to discuss the Photonic Engineering Programme offered by School of Microelectronic Engineering (SoME), Universiti Malaysia Perlis (UniMAP). The method of accreditation was implemented based on Outcome-Based Education (OBE); with accreditation outcome by Malaysian Engineering Accreditation Council (EAC). Extensive attainment based on OBE of the programme was conducted to illustrate the success of the programme. This includes the programme curriculum structure, Programme Educational Objectives (PEOs) as well as the Photonic’s Programmes Outcomes (POs). The findings after the implementation of Photonic Engineering Programme have demonstrated a successful engineering program execution in the field of Photonics with the program successfully being accredited by the EAC. However, despite the accreditation success, the university has decided to shut down the program due to low intake of students. There is no affirmation that the programme could continue if student intakes are not up to the requirement which in this case most likely due to the low interest and unfamiliar name of Photonics programme among the new generation as potential undergraduate engineering students.